2018
DOI: 10.1186/s12940-018-0389-7
|View full text |Cite
|
Sign up to set email alerts
|

Heat/mortality sensitivities in Los Angeles during winter: a unique phenomenon in the United States

Abstract: BackgroundExtreme heat is often associated with elevated levels of human mortality, particularly across the mid-latitudes. Los Angeles, CA exhibits a unique, highly variable winter climate, with brief periods of intense heat caused by downsloping winds commonly known as Santa Ana winds. The goal is to determine if Los Angeles County is susceptible to heat-related mortality during the winter season. This is the first study to specifically evaluate heat-related mortality during the winter for a U.S. city.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…This is one of the first research study investigating the morbidity burden associated with extreme heat events in the 'cooler' seasons in southern California. The only previous study to our knowledge that has investigated winter heat and health demonstrated that high winter temperature is associated with increased relative risk for mortality in Los Angeles County (Kalkstein et al 2018). Our study adds to these findings by demonstrating an explicit connection to a specific weather patter (i.e.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This is one of the first research study investigating the morbidity burden associated with extreme heat events in the 'cooler' seasons in southern California. The only previous study to our knowledge that has investigated winter heat and health demonstrated that high winter temperature is associated with increased relative risk for mortality in Los Angeles County (Kalkstein et al 2018). Our study adds to these findings by demonstrating an explicit connection to a specific weather patter (i.e.…”
Section: Discussionsupporting
confidence: 55%
“…These studies indicate that even moderate heat drives health impacts. Moreover, it has been recently suggested that the health burden of relative heat extends beyond the summer season; one study found higher mortality in the presence of hot and dry conditions in Los Angeles County during the winter months, associated with 4.4 total excess deaths per day (Kalkstein et al 2018). However, by focusing on all-cause mortality, this previous study did not capture heat-morbidity signals or consider specific diagnoses, which may underestimate the overall impact of heat.…”
Section: Introductionmentioning
confidence: 84%
“…Examination of projected health risks due to future wildfire risk and changes in SAW is warranted. Confounding the smoke‐health impacts associated with SAW and wildfires, SAW also drive coastal heat waves that incur their own health risks (Kalkstein et al, ), which will change in a warmer future as SAW‐driven heat waves become less frequent (Guzman‐Morales & Gershunov, ) but hotter (Hughes et al, ). The ventilation effect of SAW without wildfires, meanwhile, should be beneficial to respiratory health—a hypothesized effect to be examined and quantified in future research.…”
Section: Discussionmentioning
confidence: 99%
“…It would also omit all extreme temperature anomalies that fall outside of the core of summer, e.g., the March 2012 event across eastern North America that brought some of the most anomalous conditions seen in recent decades relative to the time of year, yet values that, when compared to an overall annual temperature curve, do not stand out as extreme (e.g., March 2012, [19]). It would also likely neglect events in relatively unique climates, such as the extreme warmth that sometimes affects southern California in the middle of winter due to downsloping easterly winds from the Sonoran Desert, which has been shown to increase human mortality [20,21,22].…”
Section: Introductionmentioning
confidence: 99%